The Effect of Learning Facilities and Students Creativity on Learning Outcomes of Chemistry Subject of Students at Tenth Grade of Light Vehicle Engineering Skill Program of SMK Bala Keselamatan Palu - Halawa, Adrianus; Said, Irwan; Afadil (Universitas Tadulako, 2017)
This research aims to obtain information about the effect of (1) learning facilities on chemistry learning outcomes of the student in tenth grade of light vehicle engineering skill program of SMK Bala Keselamatan Palu; (2) students creativity on chemistry learning outcomes at Tenth Grade of Light Vehicle Engineering skill ProgramÂ SMK Bala Keselamatan Palu; (3) learning facilities and students creativity on chemistry learning outcomes at Tenth Grade of light vehicle Engineering skill Program at SMK Bala Keselamatan Palu; The population in this research was all students at Tenth Grade of Light Vehicle Engineering Skill Program of SMK Bala Keselamatan Palu Academic Year 2016-2017 amounted to 91 students. The sampling technique was done by total sampling. Chemistry learning outcomes data were obtained from the average daily test results, learning facility data, and students' creativity using questionnaires. Data were analyzed by using regression and correlation analysis SPSS assisted. In testing, the first and second hypotheses used simple linear rejection analysis and the significance level of Â = 0.05. The results showed that there are significant effects between (1) learning facilities on chemistry learning outcomes; (2) students' creativity on chemistry learning outcomes; (3) learning facilities and students' creativity on the chemistry learning outcomes.